2020
DOI: 10.1177/1535370220959738
|View full text |Cite
|
Sign up to set email alerts
|

ADMA (asymmetric dimethylarginine) and angiogenic potential in patients with type 2 diabetes and prediabetes

Abstract: Asymmetric dimethylarginine is an endogenous competitive inhibitor of nitric oxide synthase and marker of endothelial dysfunction, but the question remains as to whether asymmetric dimethylarginine is a marker of cardiovascular episodes or their independent risk factor. ADMA/DDAH (dimethylaminohydrolase) pathway regulates vascular endothelial growth factor (VEGF)-mediated angiogenesis due to its impact on the NO formation. The aim of the study was to assess the concentrations of asymmetric dimethylarginine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In contrast, at T8 the ADMA levels were similar to that measured at T0. An increase of ADMA following OGTT has been shown both in subjects with normal glycemia and with impaired glucose tolerance [ 48 ] and high levels of ADMA have been detected not only in patients with diabetes, but also in prediabetics [ 57 ]. In this context, it has been suggested that the high ADMA levels may be an epiphenomenon associated with high glucose levels, a documented cause for the increase of ADMA via inhibition of intracellular oxidative stress-dependent dimethylarginine dimethylaminohydrolase activity [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, at T8 the ADMA levels were similar to that measured at T0. An increase of ADMA following OGTT has been shown both in subjects with normal glycemia and with impaired glucose tolerance [ 48 ] and high levels of ADMA have been detected not only in patients with diabetes, but also in prediabetics [ 57 ]. In this context, it has been suggested that the high ADMA levels may be an epiphenomenon associated with high glucose levels, a documented cause for the increase of ADMA via inhibition of intracellular oxidative stress-dependent dimethylarginine dimethylaminohydrolase activity [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ADMA have been identified not only in advanced DR but also in individuals at the prediabetic and diabetic stages. This observation suggests that ADMA likely plays a crucial role in both the initiation and advancement of DR [81,97]. Further studies that involve larger patient populations to better understand the role of plasma ADMA levels in the development and progression of DR are needed.…”
Section: Asymmetric Dimethylargininementioning
confidence: 99%
“…ADMA and its enantiomer, symmetric N G ,N 0G -dimethyl-L-arginine (SDMA), are strong predictors of cardiovascular events and death in a range of illnesses (3,4). Not only individuals with type 2 diabetes mellitus (DM), but also those with prediabetes, have been shown to have significantly elevated concentrations of ADMA compared with healthy controls (5).…”
Section: Introductionmentioning
confidence: 99%